Pain experienced by patient during epidural insertion using 16-gauge versus 18-gauge epidural needles - Alam, Tanveer; Qureshi, Rabeea Sajid; Saad-Ur-Rehman (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the intensity of insertion-site pain between epidural catheterisation with 16-gauge needle and with 18-gauge needle at various time points, and the number of attempts taken to locate the epidural space while using either of the needles. Method: The single-blind prospective study was conducted from August 2019 to January 2020 at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised adult patients of either gender with American Society of Anaesthesiologist grade I-III status requiring thoracic epidural for elective abdominal procedures. The patients were divided into two groups using simple randomised sampling into group A receiving 16-gauge and group B receiving 18-gauge epidural. The intensity of insertion-site pain was noted at the time of insertion, at 24 hours and one week after the insertion. The number of attempts taken to locate the epidural space was also noted for the 2 groups. Data was analysed using SPSS 23. Results: Of the 135 patients enrolled, 126(93.3%) completed the study. There were 63(50%) subjects in group A; 30(47.6%) males, 33(52.3%) females, overall mean age 46.81±10.94. The remaining 63(50%) subjects were in group B; 22(34.9%) males, 41(65%) females, overall mean age 44.89±11.10 (p>0.05). Pain scores did not differ significantly on comparative analysis between groups (p>0.05). Similarly, number of patients requiring 2 or more attempts for successful epidural catheter insertion was not significantly different between the groups (p>0.05). Conclusion: The difference in pain scores or number of attempts for 16-guage or 18-guage groups were not significant.